2014
DOI: 10.1007/s00540-014-1850-6
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic preconditioning prevents lipopolysaccharide-induced liver injury through inhibition of NF-κB activation in mice

Abstract: The results demonstrate that RIPC has protective effects in liver injury via attenuation of TNF-α production in LPS-induced sepsis. The suppressive effect on TNF-α production may be mediated through inhibition of NF-κB activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…It is reported that sevoflurane can alleviate oxidative stress in I/R organ [32], which may attenuate I/R injury. Alternatively, anti-inflammatory properties of RIPC may be associated with the inhibition of the NF-κB by suppressing its nuclear translocation [33]. Moreover, less secretion of inflammatory cytokines was observed in SPC combined RIPC group compared with those in SPC or RIPC groups.…”
Section: Discussionmentioning
confidence: 95%
“…It is reported that sevoflurane can alleviate oxidative stress in I/R organ [32], which may attenuate I/R injury. Alternatively, anti-inflammatory properties of RIPC may be associated with the inhibition of the NF-κB by suppressing its nuclear translocation [33]. Moreover, less secretion of inflammatory cytokines was observed in SPC combined RIPC group compared with those in SPC or RIPC groups.…”
Section: Discussionmentioning
confidence: 95%
“…Reperfusion was accomplished by cutting the elastic rings with scissors, confirmed by the disappearance of blue color to the limbs (Figure A1) as described previously [86,87,88]. The mice were anesthetized with isoflurane in O 2 /N 2 O (5% isoflurane for induction and 2%–3% to maintain anesthesia) during RIPC treatment and treatment consisted of three cycles of 4-min ischemia interspersed with 4-min reperfusion.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were randomly assigned to be either controls or to undergo remote IPC in which blood flow to a hind limb was occluded with a rubber band three times for ten minutes each time and separated by a ten minute period of reperfusion. Remote IPC was found to inhibit NF-κB activity with concomitant attenuation of TNF-α expression, neutrophil accumulation, and microabscess formation in the liver, thus protecting the liver from subsequent IR insult (Shin et al, 2014[69]). Finally, IPC was shown to attenuate expression of TNF-α and ICAM-1 in hepatocytes using a murine model of IR.…”
Section: Ipc Inhibits Expression Of Nf-κb and Proinflammatory Cytokinmentioning
confidence: 99%